2017
DOI: 10.1016/j.laa.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Numerically safe Gaussian elimination with no pivoting

Abstract: Gaussian elimination with no pivoting and block Gaussian elimination are attractive alternatives to the customary but communication intensive Gaussian elimination with partial pivoting 1 provided that the computations proceed safely and numerically safely, that is, run into neither division by 0 nor numerical problems. Empirically, safety and numerical safety of GENP have been consistently observed in a number of papers where an input matrix was pre-processed with various structured multipliers chosen ad hoc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…This continues our earlier study of dual problems of matrix computations with random input, in particular Gaussian elimination where randomization replaces pivoting (see [PQY15], [PZ17a], and [PZ17b]). We further advance this approach in [PLSZa], [PLa], [PLb], and [LPSa].…”
Section: Introductionsupporting
confidence: 65%
“…This continues our earlier study of dual problems of matrix computations with random input, in particular Gaussian elimination where randomization replaces pivoting (see [PQY15], [PZ17a], and [PZ17b]). We further advance this approach in [PLSZa], [PLa], [PLb], and [LPSa].…”
Section: Introductionsupporting
confidence: 65%
“…Parker also observed that structured random matrices (such as the randomized trigonometric transforms from Section 9.3) allow us to perform the preconditioning step at lower cost than the subsequent Gaussian elimination procedure. Parker (1995) inspired many subsequent papers, including (Baboulin, Li and Rouet 2014, Trogdon 2017, Demmel et al 2012, Baboulin, Dongarra, Rémy, Tomov and Yamazaki 2017 and (Pan and Zhao 2017). Another related direction concerns the smoothed analysis of Gaussian elimination undertaken in (Sankar, Spielman and Teng 2006).…”
Section: General Linear Solversmentioning
confidence: 99%
“…§17. General linear solvers Parker (1995) inspired many subsequent papers, including (Baboulin, Li and Rouet 2014, Trogdon 2017, Demmel et al 2012, Baboulin, Dongarra, Rémy, Tomov and Yamazaki 2017, Pan and Zhao 2017. Another related direction concerns the smoothed analysis of Gaussian elimination undertaken in (Sankar, Spielman and Teng 2006).…”
Section: General Linear Solversmentioning
confidence: 99%
“…Several methods that are often used to solve systems of linear equations are the Gaussian and Gauss-Jordan elimination methods. Research on this method has been carried out, including research on (Baier et al, 2020;Ding and Schroeder, 2020;Schork and Gondzio, 2020;Pan and Zhao, 2017;Alonso et al, 2010;Geng et al, 2013). Then some research on Gauss-Jordan elimination can be seen in (David, 2016;Ma and Li, 2017;Anzt et al, 2018;Sheng, 2018), Based on the explanation and research, this paper focuses on balancing chemical reactions using a system of linear equations with the Cramer method and Gauss-Jordan elimination to see that a system of linear equations can be used to find the coefficient of each compound in chemical reaction equations.…”
Section: Introductionmentioning
confidence: 99%